Influence evaluation of ionic liquids on the alteration of nitrification waste for thermal stability. (April 2023) - Yang, Na; Tang, Yan; Wu, He; Shu, Chi-Min; Xing, Zhi-Xiang; Jiang, Jun-Cheng; Huang, An-Chi
Abstract: Nitrification waste (NW) is the processed product of nitro compounds, flammable and explosive, and is prone to accidents due to thermal runaway. Ionic liquids (ILs) are widely used as flame retardants and have a good inhibitory effect. The effect of 1-butyl-3-methylimidazole hexafluorophosphate and 1-butyl-3-methylimidazole tetrafluoroborate as humectants on the thermal stability of NW was investigated in this paper. The microstructure and properties of the ionic liquid hybrid NW were first investigated using scanning electron microscopy. Secondly, thermogravimetric experiments were carried out on the ionic liquid mixed NW by thermogravimetric-infrared spectroscopy to analyze the decomposition law. Finally, six advanced linear regression thermokinetic models were used to calculate its apparent activation energy, pre-exponential factor, and other thermokinetic parameters, and the reaction model was simulated through multiple linear regression. The experimental research results in this paper can provide a reference for the storage and disposal of nitro compounds and their wastes. Highlights: Using [Bmim][PF6] and [BMIM]BF4 to inhibit the thermal runaway reaction of NW. The parameters of various kinetic models were calculated. To evaluate the effect of [Bmim][PF6] and [BMIM]BF4 relative to water as a humectant on the thermal stability of NW-D. A multiple linear regression model of NW's thermal decomposition was established based on the TGA experimental data.